New fiscal rules for the Czech Republic: Analysis of the proposal - Jaromir Baxa; Michal Paulus (Charles University in Prague, Institute of Economic Studies (IES), 2016)
We assess the proposal for a new fiscal framework that is currently being negotiated in the Parliament of the Czech Republic. The new framework contains the following elements: an expenditure rule that aims to restrain the growth of expenditures through cyclically adjusted revenues and a debt brake at a debt level corresponding to 55% of GDP to avoid unsustainable debt levels. Additionally, this set of rules shall be complemented by the Fiscal Council. Our assessment focuses on evaluating the performance of the new framework using two types of counterfactuals if it had been implemented a decade ago. In general, although we confirm the positive effects of the proposed framework, we also raise several concerns, primarily related to the effects of the rule on the ability of the public finances to operate as a macroeconomic stabilization policy.
Keywords: 330